Natural convection in a differentially heated enclosure having two adherent porous blocks saturated with a nanofluid - Astanin, Marina S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Springer Heidelberg, 2017)
Laminar natural convection in a square cavity having two centered adherent porous blocks filled with an alumina/water nanofluid under the effect of horizontal temperature gradient is studied numerically. Each porous block has the unique values of the porosity and permeability. Water-based nanofluids with alumina nanoparticles are chosen for investigation. The control characteristics of this study are the Darcy number of the first porous block (10(-7) <= Da(1) <= 10(-)3), the dimensionless porous blocks size (0.1 <= delta <= 0.4) and nanoparticles volume fraction (0 <= phi <= 0.04). The developed computational code has been validated comprehensively using the grid independency test and experimental data of other authors. The obtained results revealed the heat transfer enhancement at the hot wall with the Darcy number, while a growth of the porous layers size reduces the heat transfer rate at this hot wall. The behavior of the average Nusselt number at the right cold wall is opposite.
Keywords: Flow; Cavity; Baffles; Simulation; Channel; Tiwari